2016
DOI: 10.1002/cpnc.1
|View full text |Cite
|
Sign up to set email alerts
|

C‐C Bond Formation: Synthesis of C5 Substituted Pyrimidine and C8 Substituted Purine Nucleosides Using Water Soluble Pd‐imidate Complex

Abstract: The synthesis of a highly efficient, water soluble [Pd(Sacc)2 (TPA)2 ] complex for C-C bond formation is described. Additionally, application of the [Pd(Sacc)2 (TPA)2 ] complex for Suzuki-Miyaura arylation of all four nucleosides (5-iodo-2'-deoxyuridine [5-IdU], 5-iodo-2'-deoxycytidine [5-IdC], 8-bromo-2'-deoxyadenosine, and 8-bromo-2'-deoxyguanosine) with various aryl/heteroaryl boronic acids in plain water under milder conditions is demonstrated. © 2016 by John Wiley & Sons, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…6 Accordingly, several research groups such as Koomen et al, 20 Lanver and Schmalz, 21 and Lakshman et al, 22 as well as our group have reported the amination using palladium catalysis with limited scope and reactivity. 23 Excellent reactivity of the developed Cu(II)/PTABS catalytic system could therefore serve the double purpose of improving reactivity and providing a cheaper alternative to the expensive palladium catalyst precursors.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…6 Accordingly, several research groups such as Koomen et al, 20 Lanver and Schmalz, 21 and Lakshman et al, 22 as well as our group have reported the amination using palladium catalysis with limited scope and reactivity. 23 Excellent reactivity of the developed Cu(II)/PTABS catalytic system could therefore serve the double purpose of improving reactivity and providing a cheaper alternative to the expensive palladium catalyst precursors.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The yield% in both cases was identical using precatalyst 4 (90 %) with the product subsequently hydrolyzed to carboxylvinyl 2′‐deoxyuridine (CVU‐90 %), which was further subjected to bromination using N ‐bromosuccinimide (NBS) to yield BVDU in an overall 72 % (identical yields obtained for both 5.0 mmol and 10 mmol reactions) [19b] . Compared to the literature reports, the catalytic protocol developed using precatalyst 4 was far superior and helped achieving an enhancement in the overall yield of the final product [19d] …”
Section: Palladium Complexes Of Pta For Nucleoside Modificationsmentioning
confidence: 99%
“…Subsequently, the catalyst system was tested for Suzuki‐Miyaura coupling of all the four nucleosides with different arylboronic acids providing an array of substituted nucleosides in good to excellent yields [19d] . Despite the success achieved with the coupling reactions, the catalyst system failed to provide recyclability which was attributed to a relatively low water solubility as one possible reason.…”
Section: Palladium Complexes Of Pta For Nucleoside Modificationsmentioning
confidence: 99%
“…Purines are the basic structural units in nucleic acids and play a vital role in many life‐governing processes such as anti‐platelet aggregation activity (Liu et al., ). Therefore, the structural modifications and synthesis of purine‐based motifs (Gayakhe et al., ) have been a focus of attention by researchers from academia as well as industries (Lagisetty, Russon, & Lakshman, ; Verdugo et al., ).…”
Section: Commentarymentioning
confidence: 99%